Deserts of disadvantage: the diffuse effects of structural disadvantage on violence in urban communities - Johnson, Lallen T. (Crime & delinquency, 2018)
We advance discussion of structural inequality by operationalizing “concentrated” disadvantage in terms of highly disadvantaged communities located at the spatial core of contiguous areas of high disadvantage, and by testing the extent to which such location achieves an independent effect on violence. Using exploratory spatial data analysis and count modeling, we show that highly disadvantaged communities located at the center of a contiguous ghetto have significantly higher rates of violence than other highly disadvantaged communities, but that this relationship is moderated by structural disadvantage. In addition to finding a significant interaction between these “deserts” of disadvantage and structural disadvantage, as they relate to violent crime, we also observe that in desert communities, disadvantage has a diminishing effect on violence.